Development and Validation of the Gay-Specific Intraminority Stigma Inventory (G-SISI): Initial Evidence Underpinned by Intraminority Stress Theory - Benjamin F. Shepherd; Justin L. Maki; David G. Zelaya; Şeniz Warner; Adriana Wilson; Paula M. Brochu (European Journal of Investigation in Health, Psychology and Education, 2023)
There is currently a lack of measures testing intraminority stress within gay men. Therefore, the current study sought to develop and psychometrically test the Gay-Specific Intraminority Stigma Inventory (G-SISI). Based on a content review of the literature and a panel of experts, a pool of items assessing gay men’s perceived exposure to a range of discriminatory attitudes from other gay men was generated. Utilizing a randomly split sample of 1723 gay men between the ages of 19 and 79 years, an exploratory factor analysis was first performed (n = 861). The remaining unexamined data were then used to conduct a confirmatory factor analysis (n = 862). The results support a six-factor model: (1) Age Stigma, (2) Socioeconomic Stigma, (3) Gay Non-Conformity Stigma, (4) Racial Stigma, (5) Gender Expression Stigma, and (6) Body Stigma. Cronbach’s alpha for the total scale was 0.90 and for the subscales ranged from 0.60 to 0.85. Sociodemographic factors and measures of community involvement were differentially associated with the G-SISI subscales, providing evidence of construct validity. The findings demonstrate initial support for the dimensionality and validity of the G-SISI, which targets modifiable factors (e.g., identity-based stigma) that may increase stress and reduce community coping resources among gay men with diverse identities.